PENGARUH MODEL KOOPERATIF NUMBERED HEADS TOGETHER BERBANTUAN PICKER WHEEL TERHADAP HASIL BELAJAR PENDIDIKAN PANCASILA KELAS III SDN 066650 MEDAN KOTA - Aulia Munthe, Diva; Masri Perangin-angin, Laurensia; Lubis, Wildansyah; Winara; Gandamana, Apiek (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Numbered Heads Together (NHT) cooperative learning model assisted by Picker Wheel media on Pendidikan Pancasila learning outcomes of third-grade students at SDN 066650 Medan Kota. Preliminary data showed that only 40% of the 40 third-grade students reached the minimum mastery criterion (KKTP), indicating low learning outcomes under conventional, teacher-centered instruction. This research used a quantitative approach with a quasi-experimental method and a Nonequivalent Control Group Design, involving an experimental class (III-B, n=20) taught with NHT assisted by Picker Wheel and a control class (III-A, n=20) taught conventionally, selected through total sampling. The instrument consisted of 30 multiple-choice items, of which 25 items were declared valid (rcount > 0.443) with a reliability coefficient of 0.89 (very high category). Data were analyzed using Jamovi version 2.7 through Shapiro-Wilk normality test, Levene's homogeneity test, and an independent samples t-test. The results showed that the mean score of the experimental class increased from 47.0 (pretest) to 81.6 (posttest), a gain of 34.6 points, with mastery level rising from 0% to 85%. The control class increased from 47.4 to 66.4, a gain of 19.0 points, with mastery rising from 0% to 45%. The independent samples t-test yielded t = 4.37, df = 38, p < 0.001, and a mean difference of 15.2 points, indicating a statistically significant effect. It is concluded that the NHT cooperative learning model assisted by Picker Wheel media has a significant positive effect on the Pendidikan Pancasila learning outcomes of third-grade elementary school students.